Case report: Management of generalized infection and draining tracts of the frontomaxillary region in a dog - Wolfs, Elias; Kot, Ching Ching Shirley; Vapniarsky, Natalia; Arzi, Boaz (Frontiers in Veterinary Science, 2024)
Objective: To report the surgical and medical management of generalized chronic maxillofacial infection with multiple intra-and extraoral draining tracts in a dog.Case summary: A 6-year-old, male neutered pit bull terrier dog underwent a staged procedure. First, a diagnostic work-up including hematologic and biochemical analysis, conventional computed tomography (CT) with contrast of the skull, and rhinoscopic evaluation of the fistulous draining tracts was performed. Samples were obtained for histopathological, microbial, and fungal testing. Second, a four-week course of antimicrobials based on culture and sensitivity results was administered. Third, an extraoral approach to soft tissue reconstruction was accomplished as a first stage in the repair process. Finally, an intraoral approach to repair the oronasal fistulous draining tracts was performed. A 6-month follow up skull CT revealed various stages of repair and remodeling and adequate soft tissue healing.A staged procedure is a suitable option to treat chronic and generalized frontal and maxillary infection with multiple intra-and extraoral fistulous draining tracts in the dog.